Proposed Improvements of Air Conditioner Preventive Maintenance In The Coal Mining Industry By Utilizing DMAIC Methodology - Rahmawati, Isadora; Wibisono, Dermawan (Dinasti Publisher, 2025)
The air conditioner (AC) serves as an enabling facility to support the continued operation of coal mining activities at PT Bukit Asam, Tbk (PTBA) Tanjung Enim site, particularly at the substation, mine switch station, server room, and other work facilities. Although Preventive Maintenance (PM) of AC has been fully implemented every month, the Corrective Maintenance (CM) rate remains high. This research aims to determine the causes of the high number of work orders (WO) for CM in AC, how to design an appropriate PM and CM schedule that can be implemented to be more effective in reducing failure rates, and recommendations that can be propose to improve the reliability of AC systems in coal mining areas. The method used is the DMAIC (Define–Measure–Analyze–Improve–Control) approach, combined with FMEA (Failure Mode and Effects Analysis) and risk-based maintenance principles. Data was analyzed from the monthly report, work order history from July to December 2024, observations, and semi-structured interviews with related management and users in the operational department. Research findings indicate that 55% of activities are non-value-added, while only 45% of activities are value-added. FMEA analysis identified several failure modes, including filters that easily become dirty, the lack of PM monitoring and evaluation, not yet to conduct an environmental risk assessment for air conditioner maintenance on the mining site, and the movement between departments is far away. The implementation of risk-based maintenance for work order CM, from January to June 2025, has classified risks into high, moderate to high, moderate, and low to moderate risk locations that directly impact operations, and has positive results with a sigma level increasing from 2.88 to 3.29. Propose improvement recommendations include reorganizing the PM schedule by location and implementing digital tagging forms for units to report maintenance activities.